Pidgin english spoken by papua new guinea people in youtube videos - Wengke, Febrianus; Putra, I G. B. Wahyu Nugraha; Jendra, I Made Iwan Indrawan (Journal of Language and Applied Linguistics, 2022)
This research deals with Pidgin English spoken by Papua New Guineans found in YouTube videos. This study aims to identify the types of sentences in Pidgin English used by the people of Papua New Guinea and the differences between Pidgin English from Standard English. This study uses qualitative methods to carry out a clear and organized description of the problems identified. The data is taken from the narratives of Papua New Guineans found in YouTube videos. Applying Muhlhausler's (1978) theory to analyze the types of sentences used by Papua New Guineans found in YouTube videos and theory by Aitchison (1991) to distinguish between Pidgin English and Standard English. This study finds data based on the first study problem about sentence types such as the equative sentence mi citizen bilong la country 'We are the community on this country,' locative sentence yupela from East Sepik Province 'you are from East Sepik Province,' intransitive sentence mipela i simenim i go bek 'I am comment to return, and ' transitive sentence mi wokim ho na long em 'I am help them all.' The data contained in the second problem of research on differences in Pidgin English from Standard English such as the phonology em planti samting 'there are more,' the syntax so mi makim PNG 'so I marked PNG,' the dispela is lexicon of 'this is/is.'